Water harvesting as a key for understanding adapted ancient livelihoods in an arid environment – Approaches to dryland archaeology in the Eastern Marmarica (NW-Egypt). (December 2019) - Vetter, Thomas; Rieger, Anna-Katharina
Abstract: The Marmarica, an arid region in NW-Egypt between the Jebel el Akhdar to the west and the Nile Valley to the east, offers rich evidence for understanding the interlinkages of scarce natural resources, above all water and soil and their human utilization in antiquity. Analysing the natural hydrological regime depending on rainfall, soils and topography in the region and the man-made interventions lies at the heart of this landscape archaeological study. Integrating evidence from various disciplines (hydrology, geomorphology, soil science, archaeobiological methods, ceramic studies, evaluation of literary sources based on papyri) and from various periods (late 2nd millennium BCE to 7th century CE) allowed for the reconstruction of the ancient water management and the related life-strategies. An assessment of climatic conditions and morphological features of the Eastern Marmarica is provided, where wadis, alluvial fans, but also lateral wadi slopes and to a certain extent even parts of the vast tableland plains represent favourable geomorphological units for water harvesting and hence, agricultural production. Yet, a characteristic that sets the Marmarican systems apart from those in other arid regions are cultivated terrace systems (run-in areas) that are located on lower lateral valley slopes and even on the tableland plains. The results provide insights into the long-term responses of the inhabitants in antiquity to catchment hydrology by water harvesting and the effects of their interventions, the adapted livelihoods, regional specialization of rural production and intra- and interregional exchange of goods. However, new questions arose regarding i) the implications of the ancient water management strategy for the social organisation of the local people, ii) the destinations of locally produced pottery, iii) the habitational and land-use patterns before the Graeco-Roman period, iv) the role and range of climatic shifts, and v) reasons for the decline of the sophisticated runoff management. Highlights: Models East-Marmarican rural livelihoods in Graeco-Roman times. Analyses the regional particularity of water harvesting induced cropping areas for surplus production. Proposes a more detailed chronology of runoff agriculture in the Eastern Marmarica. Interlinks ecological and anthropogenic drivers of change for adapted livelihoods. Discusses socio-economic organisation in an ecologically and demographically marginal region.